SWOT ANALYSIS FOR STARTUP BUSINESSES - Ananda, Rosmita Dewi; Bahiroh, Eloh (PT Larva Wijaya Penerbit, 2023)
Companies must always pay attention to market conditions and compete more fiercely when determining strategy in the face of growing global competition. One method for determining each force's level of competitiveness is through competitive strategy, SWOT analysis effectively can help determine a company's competitive strategy by identifying the company's strengths, weaknesses, opportunities, and threats to its continued existence. The question that needs to be answered by this study is,